2001
DOI: 10.1063/1.1343522
|View full text |Cite
|
Sign up to set email alerts
|

A direct comparison between terahertz time-domain spectroscopy and far-infrared Fourier transform spectroscopy

Abstract: We perform a comprehensive comparison between terahertz ͑THz͒ time-domain spectroscopy and conventional far-infrared Fourier transform spectroscopy, including radiation source, detector, signal to noise ratio, bandwidth, availability, applications, and their own uniqueness. In terms of signal to noise ratio, THz time-domain spectroscopy is advantageous at low frequencies under 3 THz, while Fourier transform spectroscopy works better at frequencies above 5 THz. In addition, we provide a detailed discussion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
108
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(109 citation statements)
references
References 10 publications
0
108
0
1
Order By: Relevance
“…THz-TDS is advantageous at low frequencies under 3 THz, while FIR FT spectroscopy works better at frequencies above 5 THz [21]. In order to fit precisely the measured THz-TDS data in the 0.25-2 THz frequency range and also to be consistent with the high frequency FIR FT reflectance data (determined by Sotome et al), the modification of some Lorentz-model parameters (Table 1) is needed.…”
Section: Resultsmentioning
confidence: 99%
“…THz-TDS is advantageous at low frequencies under 3 THz, while FIR FT spectroscopy works better at frequencies above 5 THz [21]. In order to fit precisely the measured THz-TDS data in the 0.25-2 THz frequency range and also to be consistent with the high frequency FIR FT reflectance data (determined by Sotome et al), the modification of some Lorentz-model parameters (Table 1) is needed.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that at frequencies below 3 THz, the SNR of the FTS is worse than that of time-domain spectroscopy (TDS) [2]. The FTS system could still be used to study materials in some applications provided that there is enough SNR.…”
Section: Measurements Of Filtersmentioning
confidence: 99%
“…We studied the properties of heterodyne detectors including superconductor mixers and semiconductor harmonic mixers, direct detectors including an InSb semiconductor bolometer, superconducting tunnel junctions and the Golay cell, and sources including Gunn oscillators and a microwave source with its multipliers, as well as various materials and passive devices including Si wafers and metal mesh filters. Because of its multiplex and etendue advantages, Fourier transform spectroscopy has become the most efficient way to evaluate the properties of signal sources, samples and detectors in the terahertz (THz) range [1][2][3]. The multiplex advantage is that the interferometer receives information from the entire range of a given spectrum during each time element of a scan, whereas a grating spectrometer receives information from only a narrow band of the spectrum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bolometric detectors only operate under vacuum at liquid-helium temperatures [10]. Fourier transform infrared (FTIR) spectroscopy does offer spectroscopic information down to about 1 THz, but not into the GHz regime [11]. Research continues into many sources and detectors in the THz band, including germanium lasers, gas -vapor lasers, quantum cascade lasers and backward-wave oscillators [12 -15].…”
Section: Thz-tdsmentioning
confidence: 99%